Is Self-Determined Motivation a Useful Agent to Overcome Perceived Exercise Barriers in Patients With Type 2 Diabetes Mellitus? - Kang, Heon Jin; Wang, John Chee Keng; Burns, Stephen Francis; Leow, Melvin Khee-Shing (Frontiers in Psychology, 2021)
Background: Devising a program to increase physical activity (PA)/exercise behavior in patients with type 2 diabetes mellitus (T2DM) can meet with limited effectiveness in real-world settings because of the variety of barriers to PA/exercise that individuals need to overcome. An alternative approach is to explore whether targeting motivation as a facilitator may be effective to increase PA/exercise. This study aimed to understand attitudes toward perceived barriers to PA/exercise by examining individual levels of motivation, grounded on self-determination theory, in patients with T2DM. Methods: This study used an integrated approach combining qualitative and quantitative analysis. Sixteen patients with T2DM were grouped (n = 8 for each group) into either a higher self-motivation (HSM) or lower self-motivation (LSM) group via the Relative Autonomy Index. Thematic and deductive analysis were used to identify attitudes based on ten preconceived barrier themes: apathy, dislike, no priority, lack of support, health problems, lack of knowledge, unfavorable environment, tiredness, lack of time, and financial constraints. Quantitative analysis was to assess statistical differences in the volume of PA/exercise across the two groups, and a mixed-methods analysis was employed to highlight unique cases. Results: Patients in the HSM group expressed positive attitudes toward barriers to PA/exercise, while patients in the LSM group expressed a greater degree of hindrance. Although regular PA/exercise is necessary for T2DM management, patients with LSM considered PA/exercise a lesser priority displaying negative attitudes such as apathy and dislike. Conversely, patients with HSM placed greater emphasis on the benefits of PA/exercise regardless of apathy and dislike. Lack of time and health problems were commonly reported in both groups. The volume of PA/exercise corresponded to motivation levels, but there were some unique cases which arose from active commuting habits and severe health problems. Conclusion: These findings provide insights on how attitudes to perceived barriers to PA/exercise differ by levels of motivation. One insight was that examining motivation should be an essential consideration when designing practical strategies to overcome PA/exercise barriers in patients with T2DM. Lack of time and health problems exist regardless of motivation levels. Future research requires a tailored approach to managing barriers to PA/exercise in patients with T2DM.